The Effect of Problem-Based Learning Model Assisted by Audio-Visual Media on Interest and Learning Outcomes in Social Studies - Indrawati Indrawati; Suardi Suardi; Kaharuddin Kaharuddin (Journal of Educational Sciences, 2026)
This study investigates the effectiveness of integrating Problem-Based Learning (PBL) with audiovisual media in enhancing fifth-grade students’ interest and achievement in social studies. The research was motivated by the persistent predominance of teacher-centered instruction in Indonesian primary schools, which often leads to low engagement and suboptimal learning outcomes. Employing a quasi-experimental design with a pretest–posttest control group, the study involved 44 students from two Grade 5 classes in one public primary school cluster in South Sulawesi. The experimental class received PBL supported by audiovisual media, whereas the control class was taught using conventional methods without systematic media integration. Data on learning interest were collected through a validated questionnaire, and learning achievement was measured using standardized social studies tests administered before and after the intervention. The data were analyzed using descriptive statistics, independent samples t-tests, and MANOVA. The findings demonstrate that students in the PBL with audiovisual media group achieved significantly higher gains in both learning interest and social studies achievement than those in the control group (p < 0.05). These results indicate that PBL supported by audiovisual media is a promising pedagogical approach for fostering more engaging and effective social studies instruction in primary education.